(3EOGQI GdeYQaI aj GdeDSSI GdEbJUGOjI (B((3GdLRA GdKGfj(B)s - (3SejQ(B, (3YRGdOjfs ((3GdLRGFQ(B:s (3OGQ CLjGd GdQbej (B,s, 2024)
(3JfGhd gPG GdcJGH(B: (3JcfhdhLjG GdeYdheGJ hGdGJUGdGJ hOhQgG aj JWhjQ COGA GdeDSSI, JCKjQ JcfhdhLjG GdeYdheGJ hGdGJUGd Ydi feGPL GdCYeGd, eSGgeI JcfhdhLjG GdeYdheGJ hGdGJUGdGJ aj JaYjd GOGQI GdeYQaI, GdJLGQI GdGdcJQhfjI aj GdLRGFQ GdhGbY hGdJMOjGK , GdJMOjGJ GdCefjI dGfJgGc GdNUhUjI aj GdJLGQI GdGdcJQhfjI hSHd GdMeGjI GdeYdheGJjI, GdJLGQI GdGdcJQhfjI aj GdLRGFQ GdhGbY hGdBaGb, OhQ JcfhdhLjG GdeYdheGJ aj OYe EOGQI GdeYQaI, OQGSI GdYdGbI Hjf GdPcGA GdGbJUGOj hGSJQGJjLjI GdeDSSI, OhQ GdGHJcGQ aj JMSjf COGA bWGY JcfhdhLjG GdeYdheGJ hGdGJUGdGJ, aYGdjI GdPcGA GdGUWfGYj aj GdGbJUGO hJCKjQg Ydi GdJShjb GdOhdj, JfejI GdGHOGY hGdGHJcGQ aj GdeDSSI aj Xd EOGQI GdeYQaI, JMOjGJ GdPcGA GdGbJUGOj aj Xd CNdGbjGJ GdCYeGd, eSGgeI GdGHOGY hGdGHJcGQ aj JMSjf COGA GdeDSSGJ GdGbJUGOjI, hGbY GSJNOGe JcfhdhLjG GdeYdheGJ hGdGJUGd aj GdLRGFQ, JfejI egGQGJ GdJacjQ GdGHOGYj dOi GdehO GdHTQj ceONd GSJQGJjLj dRjGOI GdaYGdjI GdJfXjejI(B.s
Keywords: (3GOGQI GdeYQaIs; (3GdEOGQIs; (3GdJLGQI GdGdcJQhfjIs; (3GdeYQaIs; (3JcfhdhLjG GdeYdheGJs